2022
DOI: 10.1002/cmdc.202200331
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity‐Gene Expression Correlations and Functional Enrichment Analysis Provide Insight into the Mechanism of Action of a Platinum‐Acridine Anticancer Agent

Abstract: NCI-60 growth inhibition and gene expression profiles were analyzed using Pearson correlation and functional enrichment computational tools to demonstrate critical mechanistic differences between a nucleolus-targeting platinum-acridine anticancer agent (PA) and other DNA-directed chemotherapies. The results support prior experimental data and are consistent with DNA being a major target of the hybrid agent based on the negative correlations observed between its potency and expression levels of genes implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Moreover, recent chemosensitivity-gene expression correlations and functional enrichment analysis by Bierbach and coworkers demonstrated that BRCA1 appears to play a critical role in the processing of DNA damage produced by the plati- num-acridine anticancer agent (compound 1). 43 Like the hybrid Pt-acridine agent, the monofunctional P1-Q1 and P1-Q2 can rapidly accumulate in the nucleoli in cancer cells and lead to the quenching of de-novo rRNA synthesis and nucleolar stress. 43 Although cancer cells are inherently sensitive to agents that targeted Pol I transcription and ribosome biogenesis, they may also buffer the damage produced by these hybrid platinum agents on the nucleoli by arresting cell cycle progression and recruiting the DNA damage repair machinery.…”
Section: P1-q1 and P1-q2 Selectively Inhibited Brca1-deficient A549 C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent chemosensitivity-gene expression correlations and functional enrichment analysis by Bierbach and coworkers demonstrated that BRCA1 appears to play a critical role in the processing of DNA damage produced by the plati- num-acridine anticancer agent (compound 1). 43 Like the hybrid Pt-acridine agent, the monofunctional P1-Q1 and P1-Q2 can rapidly accumulate in the nucleoli in cancer cells and lead to the quenching of de-novo rRNA synthesis and nucleolar stress. 43 Although cancer cells are inherently sensitive to agents that targeted Pol I transcription and ribosome biogenesis, they may also buffer the damage produced by these hybrid platinum agents on the nucleoli by arresting cell cycle progression and recruiting the DNA damage repair machinery.…”
Section: P1-q1 and P1-q2 Selectively Inhibited Brca1-deficient A549 C...mentioning
confidence: 99%
“…43 Like the hybrid Pt-acridine agent, the monofunctional P1-Q1 and P1-Q2 can rapidly accumulate in the nucleoli in cancer cells and lead to the quenching of de-novo rRNA synthesis and nucleolar stress. 43 Although cancer cells are inherently sensitive to agents that targeted Pol I transcription and ribosome biogenesis, they may also buffer the damage produced by these hybrid platinum agents on the nucleoli by arresting cell cycle progression and recruiting the DNA damage repair machinery. 43 In this context, the deficiency of BRCA1 and selective Pol I inhibition would cause irreversible damage to cancer cells, ultimately leading to profound cell death.…”
Section: P1-q1 and P1-q2 Selectively Inhibited Brca1-deficient A549 C...mentioning
confidence: 99%
“…37−39 Lastly, the PAs have demonstrated a spectrum of anticancer activity distinct from that of other DNA-targeted warheads currently used in ADC payloads, including topoisomerase I poisons and anthracyclines. 7,12 Given these promising features and the renewed interest in DNA-targeted warheads in ADC payloads, 3 the PPL concept introduced here should be evaluated for targeted applications in cancer treatment with PAs.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Platinum–acridine hybrid agents (PAs) (Figure A), which are among the most potent platinum-containing anticancer agents developed to date, were designed based on this rationale. PAs inhibit replication and transcription and are efficient inducers of replication fork arrest and DNA double-strand breaks (DSBs). They accumulate in the cells’ nucleoli , and cause adducts in rRNA genes (rDNA) . This damage triggers nucleolar stress responses that likely contribute to the growth arrest in G 1 /S phase of the cell cycle and apoptosis the agents cause . Importantly, the unique spectrum of activity of PAs shares no similarities with that of other platinum-based drugs, , which provides a strong rationale for their clinical development.…”
mentioning
confidence: 99%
“…17 This damage triggers nucleolar stress responses that likely contribute to the growth arrest in G 1 /S phase of the cell cycle and apoptosis the agents cause. 18 Importantly, the unique spectrum of activity of PAs shares no similarities with that of other platinum-based drugs, 18,19 which provides a strong rationale for their clinical development.…”
mentioning
confidence: 99%